2011
DOI: 10.1111/j.1471-0528.2010.02839.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of long-term administration of sildenafil in normotensive pregnant and non-pregnant rats

Abstract: Objective To determine the effects of chronic administration of sildenafil citrateon healthy pregnant rats.Design In vivo animal experimental study.Setting Fundació n IVI-Instituto Universitario IVI, Valencia, Spain.Sample Pregnant and non-pregnant Wistarrats exposed to chronic administration of sildenafil.Methods Placental cross-barrier and feto-maternal relationship levels, maternal blood pressure, and haemodymamic effects on uterine arteries were evaluated. The effect of growth on weight and fetal tissues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
5
17
1
Order By: Relevance
“…Interestingly, SC treatment failed to increase fetal weight in the WT C57Bl/6J pups, in contrast with previous reports in sheep [14], mice [13] and rats [40], [41] which suggest an increased fetal weight in control fetuses from SC-treated mothers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SC treatment failed to increase fetal weight in the WT C57Bl/6J pups, in contrast with previous reports in sheep [14], mice [13] and rats [40], [41] which suggest an increased fetal weight in control fetuses from SC-treated mothers.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast with studies suggesting that SC increased placental weight in control Wistar rats following long-term administration [40], [41] but in agreement with recent work in mice which failed to detect any differences in placental weight following SC treatment [13]. Most other published in vivo studies examining the effectiveness of SC in FGR failed to report placental weight, and this does require further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…We have demonstrated the placental transfer of SC in a group of normotensive rats. We observed that SC appears to have a selective hypotensive effect at the onset of pregnancy, implying increased fetal blood supply, an effect that was not present in nonpregnant animal groups 11 . Moreover, the cellular mechanisms by which the inhibitors of phosphodiesterase‐5 improve endothelial function and cell survival in critical situations after ischaemia and reperfusion have been described 12 .…”
Section: Introductionmentioning
confidence: 85%
“…An animal PE model with hypertension, proteinuria and fetal growth restriction can be developed using a nonselective inhibitor of all isoforms of nitric oxide synthase (NOS) ( N ‐nitro‐ l ‐arginine methyl ester, l ‐NAME) 11,16–20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation